UNIAXIAL COMPRESSIVE STRENGTH, DRY UNIT WEIGHT AND FRACTURE PATTERNS OF ULTRABASIC ROCKS IN OTHRYS MOUNTAIN (CENTRAL GREECE): CORRELATIONS AND EVALUATION - Diamantis, K.; Karamousalis, Th.; Antoniou, Vas.; Migiros, G. (Bulletin of the Geological Society of Greece, 2007)
Ultrabasic rocks, taken from the Othrys mt. (Central Greece), are studied in this paper. The structural geology and tectonics of the study area are described. Uniaxial Compressive Strength (UCS) and dry unit weight (γ) values are calculated and fracture angles are measured. The results are statistically assessed and empirical relationships (exponential equations) between UCS and γ are presented for the ultrabasic roch, divided in Peridotites, Serpentinised Peridotites and Serpentinites. Due to the low correlation coefficient of the Serpentinised Peridotites, it was decided that the Serpentinised Peridotites and Serpentinites should be examined together. The correlation coefficient of the combined category is much better than the separate ones. Furthermore, this paper demonstrates that the majority of the ultrabasic rocks tested were breaking at one angle (φ°), which mainly fluctuated between 75° and 90°. The fracture angles correlate with previously recognised geological (mainly tectonic) structures. The observed deviations are due to pétrographie variety, structural complexity, preferred orientation of olivine and orthopyroxene and internal imprinted tectonic deformation.